Saline Waters in Miocene Western Amazonia – An Alternative View - Gross, Martin; Piller, Werner E. (Frontiers in Earth Science, 2020)
Before the onset of the modern Amazon River system, northwestern South America was shaped by an extensive wetland during the Miocene. This “Pebas mega-wetland” kept a well-renowned endemic mollusk and ostracod fauna, which initiated a persisting debate about marine ingressions reaching the center of Amazonia at that time. Due to high endemism, uniformitarian principles are hardly applicable to this biota, but also other paleontological, sedimentological, and geochemical information led to ambiguous paleoenvironmental interpretations. Here, we investigate the ostracod and foraminifer assemblages and the oxygen and carbon stable isotope compositions of their biogenic calcite from an outcrop at the cutbank of the Amazon River (NE-Peru, ∼55 km S of Iquitos). While ostracods (e.g., the genus Cyprideis) are able to calcify their carapaces along the entire salinity range, at least low saline conditions are a prerequisite for the biomineralization of calcareous foraminiferan tests. Hence, the finding of calcareous foraminifers (Ammonia, Elphidium), associated mainly with brackish water ostracods indicates the presence of saline waters. In contrast, δ18O and δ13C analyses performed on co-occurring ostracod valves and foraminiferan tests yielded constantly very light ratios. Such values refer to a pure freshwater environment and are incompatible with the interference of isotopically heavier, marine waters or a stable isotope enrichment by evaporation. Based on these contrasting data, we hypothesize that the Pebas mega-wetland was episodically influenced by saline but isotopically light groundwater discharge. Possibly, the resulting specific hydrochemistry not only contributed to the evolution of the endemic Pebasian fauna but also facilitated the sporadic settlement of euryhaline foraminifers, which mimics short-lived marine incursions.